The frequency of non tuberculosis mycobacteria among isoniazid resistant Mycobacterium isolates and the pattern of resistance to antituberculosis drugs - Praseno, Ning Rintiswati (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2010)
Non tuberculosis mycobacteria (NTM) could be the causative agents of various clinical infections, especially inimmunocompromised individuals. However, frequency of this bacteria among Mycobacterium isolates is not yeknown. Morover, their pattern of resistance to antituberculosis drugs has not been reported. The aim of the study isto determine the frequency of NTM among isoniazid resistant Mycobacterium isolates and the pattern of resistanceto antituberculosis drugs. The clinical isolates of isoniazid-resistant mycobacteria collected from several laboratoriesin Java were cultured on Lowenstein Jensen (LJ) medium and followed by drug sensitivity testing. Identification ofNTM was based on standard microbiological test: colony morphology, duration of growth, acid fast staining, andbiochemical test (niacin test and nitro benzoic acid medium test). All isolates were resistant to rifampicin, 81.20%were streptomycin resistant, and half of them were resistant to ethambutol. Pattern of resistance to the secondline antituberculosis drugs (ciprofloxacin, kanamicin, and ofloxacin) was variable with the range of 37,5%to 62,5%.In conclusion, almost all NTM isolates were resistant to rifampicin and streptomycin, whereas more than half ofisolates were resistant to the second line drugs (ciprofloxacin, kanamicin, and ofloxacin).Key words: NTM- isoniazid resistant- pattern of resistance â antituberculosi drugs